2021
DOI: 10.1108/dta-03-2020-0068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eWom on purchase intention: meta-analysis

Abstract: PurposeThe aim of this research is to combine and synthesize the findings of previous studies search for the effects of eWom on purchase intention by meta-analysis.Design/methodology/approachThe paper shows a meta-analysis process step by step. Within the scope of certain criteria, the studies in the Google Scholar and ITÜ library databases were eliminated and the results of the remaining 19 studies were analyzed in CMA (Comprehensive Meta-Analysis) program.FindingsBy conducting a meta-analysis of the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
1
6
0
1
Order By: Relevance
“…Correlations and path coefficients are more significant for connections associated with eWOM usefulness than for associations with eWOM credibility. These results resonate with past studies (e.g., Albayrak & Ceylan, 2021;Dou et al, 2012;Koci c & Radakovi c, 2019;Saleem & Ellahi, 2017).…”
Section: Sem Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Correlations and path coefficients are more significant for connections associated with eWOM usefulness than for associations with eWOM credibility. These results resonate with past studies (e.g., Albayrak & Ceylan, 2021;Dou et al, 2012;Koci c & Radakovi c, 2019;Saleem & Ellahi, 2017).…”
Section: Sem Resultssupporting
confidence: 93%
“…In today's world, word-of-mouth is a critical aspect of e-commerce since customers are highly receptive to the views of others. Electronic word of mouth (eWOM) has considerably impacted how customers make buying choices (Albayrak & Ceylan, 2021). In marketing, word of mouth (WOM) refers to consumers informing other consumers regarding products, facilities, labels, or businesses.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about negative consumers’ e-WOM were not found in some previous studies; for instance, Roy et al (2020) claimed that the e-WOM factor does not affect the green purchase intention of aging Indian consumers (Roy et al , 2020). However, some studies emphasized that e-WOM had a direct impact on green purchasing intentions (Albayrak and Ceylan, 2021; Jain et al , 2020), and other studies found that e-WOM had an indirect effect on green purchase intention (Chen et al , 2019; Choi et al , 2019; Jain et al , 2020; Leong et al , 2022; Pauliene and Sedneva, 2019). Further investigation is needed to understand why e-WOM does not influence the Vietnamese market compared to other markets.…”
Section: Resultsmentioning
confidence: 99%
“…Research indicates that consumers often gauge a product's popularity and value by the sheer number of online referrals (Bataineh, 2015). A greater quantity of eWOM signals positive social proof, exerting a favorable influence on purchase intention (Albayrak & Ceylan, 2021). Consumers tend to trust products or services with numerous positive reviews and high online visibility (Luo et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%